Cytotoxicity evaluation and the mode of cell death of K562 cells induced by organotin (IV) (2-methoxyethyl) methyldithiocarbamate compounds - Nurul Farahana Kamaludin, Nazifa Ismail, Normah Awang, Rapidah Mohamad, Norraphat Uttraphan Pim (Journal of Applied Pharmaceutical Science, 2019)
Two new organotin (IV) dithiocarbamate compounds, which are diphenyltin (IV) (2-methoxyethyl) methyldithiocarbamate (compound 1) and triphenyltin (IV) (2-methoxyethyl) methyldithiocarbamate (compound 2), were tested for their toxicity against human erythroleukemia cells (K562). The potential of both compounds to induce cytotoxicity against K562 cells was determined via MTT assay for 24 hours. The mode of K562 cells’ death induced by both compounds was determined by Annexin V-FITC/PI staining assay for 24 hours using the IC50 values obtained from the MTT assay for each compound. This study found that compound 1 and compound 2 were very toxic to K562 cells, producing IC50 values of less than 5.0 μg/cm3. Compound 1 showed higher cytotoxicity against K562 cells with an IC50 value of 4.0 μM (2.41 μg/cm3) compared to compound 2 which has an IC50 value of 8.0 μM (4.52 μg/cm3). In addition to that, both compounds were found to induce about 43.0% of K562 cell death via apoptosis. In conclusion, the compounds showed good potential to be developed into anti-leukemic agents due to their strong cytotoxicity against K562 cells leading to induction of cell death via apoptosis. Further studies on their mechanisms of action are warranted in order to explore their potential to be developed into anti-leukemic agents.
Keywords: Organotin (IV), dithiocarbamate, cytotoxicity, apoptosis, K562.